Oportunidades fiscales y financieras de las personas por la implementación de sistemas de energía solar en Colombia - Céspedes Pórtela, Angie Paola (Universidad Antonio Nariño, 2023)
Much of the research in Colombia involves industrial and commercial companies so that they contribute to the pollution of CO2 emissions that cause global warming. To mitigate this impact, the government has implemented tax incentives that are parallel to public policy tools to generate awareness. and thus help improve the quality of life of people and communities by allowing or improving access to water with electricity through solar systems and thus increase the competitiveness of the commercial and industrial sector by reducing taxes, operating costs for electricity and thus contribute to the environmental impact. As a result of this article, all the tax and financial benefits in Solar energy will be announced, revealing in which cases it is feasible to invest according to consumption and electrical cost, therefore, practical cases will be studied, making known the financial viability of the implementation of these friendly systems.